2010
DOI: 10.2519/jospt.2010.3257
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Effects of Atlanto-occipital Joint Manipulation and Suboccipital Muscle Inhibition Technique on Active Mouth Opening and Pressure Pain Sensitivity Over Latent Myofascial Trigger Points in the Masticatory Muscles

Abstract: t desiGn: A randomized controlled trial.t obJectiVe: To investigate the immediate effects on pressure pain thresholds over latent trigger points (TrPs) in the masseter and temporalis muscles and active mouth opening following atlanto-occipital joint thrust manipulation or a soft tissue manual intervention targeted to the suboccipital muscles.t bacKGRound: Previous studies have described hypoalgesic effects of neck manipulative interventions over TrPs in the cervical musculature. There is a lack of studies anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 45 publications
4
85
0
15
Order By: Relevance
“…Therefore, considering the results found in this study, we recommend the use of infrared thermography as an aid tool in assessing TMD, mainly when the objective is to determine the effect of different therapeutic resources used for the TMD treatment, such as electrotherapy 33,34 , laser therapy 35,36 and manual therapy 37,38 . Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considering the results found in this study, we recommend the use of infrared thermography as an aid tool in assessing TMD, mainly when the objective is to determine the effect of different therapeutic resources used for the TMD treatment, such as electrotherapy 33,34 , laser therapy 35,36 and manual therapy 37,38 . Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…11,21 Özellikle kas kaynaklı TMD'lerde, çiğneme sisteminde ağrı varlığı servikal omurga bozukluklarına ya da tam tersi servikal omurga bozuklarının TMD'lere sebep olabileceği vurgulanmıştır. 10 Literatür ile paralel olarak bu olguda da baş-boyun kaslarında, ayrıca skapulotorasik bölge kaslarında yumuşak doku gerginlikleri ve tetik nokta varlığı saptanmıştır. Fizyoterapi programı oluşturulur iken, yumuşak doku göz önünde bulundurularak hem çene bölgesine hem de servikal ve skapulotorasik bölgeye yönelik uygun fizyoterapi yaklaşımlarından faydalanılmış-tır.…”
Section: Discussionunclassified
“…Two studies evaluated mouth opening in asymptomatic individuals immediately after the manual therapy treatment compared to the control group. Among these, George et al [16] observed no improvement, whereas Oliveira Campello et al [29] noted significant improvement in mouth opening. Since asymptomatic individuals were assessed in these studies, the clinically significant measurement of pain-free MMO could not be used.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of a control group in this study does not allow distinction of the actual treatment effect in TMD. Oliveira Campello et al [29] reported that atlanto-occipital joint manipulation and suboccipital muscle inhibition increased PPT on the latent trigger points of masticatory muscles in asymptomatic patients immediately after application of the technique when compared to a control group. In this study, an increase of approximately 0.2 kg/cm 2 in PPT, which was not clinically significant, was observed on the latent trigger points in the trigemi- nal region.…”
Section: Discussionmentioning
confidence: 99%